Pengaruh Disiplin Kerja, Lingkungan Kerja, Dan Motivasi Kerja Terhadap Kinerja Tenaga Medis RSU Cut Mutia Kabupaten Aceh Utara - Rahmi Rahmi; Sufitrawati Sufitrawati; Nelly Nelly; Zalikha Zalikha; Riska Riska (Global Leadership Organizational Research in Management, 2024)
This research aims to determine the influence of work discipline, work environment and motivation on the performance of medical personnel at Cut Mutia RSU, North Aceh Regency. This type of research is associative research. Data collection in this research was carried out using a survey approach with a quantitative descriptive type of research by distributing questionnaires to 54 respondents, while the population used in this research was employees of the Cut Mutia RSU medical staff. Data collection techniques were carried out using interviews, questionnaires and documentation studies. The data analysis tool used in this research uses SPSS (Statistical Product Software Solution). The data analysis techniques in this research are descriptive analysis, multiple linear regression analysis, hypothesis testing using a partial significant test (t test), simultaneous significant test (F test), and testing the coefficient of determination (R2). The results of this research show that simultaneously work discipline, work environment and motivation have a positive and significant effect on employee performance at Cut Mutia RSU with the research results showing that the Fcount value is (254.089) > Ftable (2.62) and the significance level is 0.00 < 0.05